Acoustic properties of biological suspensions with non-spherical suspended droplets - LEWANDOWSKI, J. (Archives of Acoustics, 1998)
A theoretical study is made of the propagation properties of a suspension of viscous liquid droplets in a fluid medium with low viscosity. The droplets are of the form of oblate ellipsoids; the values of the material, structure and compositions parameters of the suspension are that of human blood. From the presented results of the analysis it can be seen that the propagation velocity and attenuation of ultrasound strongly depend on the blood composition, mechanical properties of the blood components as well as the ultrasonic frequency.